Cover Image. Issue 2 (4th February 2020) - Hu, Feiyu; Warren, Jim; Exeter, Daniel J.
Abstract : The cover image is based on the Original Report* Interrupted time series analysis on first cardiovascular disease hospitalization for adherence to lipid‐lowering therapy by Feiyu Hu** et al., https://doi.org/10.1002/pds.4916 .***